RECONCEPTUALISATION OF NOVATION IN CONTRACT LAW: A REVIEW OF THE PRACTICE OF CONVERTING LOCAL GOVERNMENT PROJECT AGREEMENTS INTO SHARES - Anita Kamilah; Hesti Dwi Astuti; Wandi Setiawan; Delis Nia Nadiyana; Amani Sabila (Proceeding International Conference on Social Sciences, 2026)
Novation, as a form of contract termination, plays an important role in addressing obstacles to local government project development due to default or force majeure. Novation has legal consequences not only for the legal relationship between the parties but also for the subject matter of the contract that had previously been established. This study plays an important role in examining: (1) the reconceptualisation of novation through share conversion from a contract law perspective; and (2) the form of novation in the conversion of local government project agreements into shares. The approach used in this research is juridical, descriptive analytical research specification, and the types and sources of data consist of secondary data supported by primary legal materials, secondary legal materials, and tertiary legal materials. Data analysis is conducted qualitatively. The results of the study show that the concept of novation is no longer only interpreted as the replacement of debt with debt, but there is a transformation of the form of agreement into a different type of legal relationship through capital/share ownership in a company. The conversion of local government project agreements into shares falls under objective novation, as well as passive subjective novation and passive subjective novation.